a patrat -b patrat=45
a+b=15
5a-5b=?
Răspunsuri la întrebare
Răspuns de
2
Răspuns de
2
a² - b² =45
(a+b)(a-b) = 45
a+b = 15
inlocuim in ecuatia initiala :
15(a - b) =45
a-b = 45 : 15
a-b = 3
5a -5b = 5(a - b) = (inlocuim pe "a-b" cu 3)
5 × 3 = 15 => 5a - 5b = 15
(a+b)(a-b) = 45
a+b = 15
inlocuim in ecuatia initiala :
15(a - b) =45
a-b = 45 : 15
a-b = 3
5a -5b = 5(a - b) = (inlocuim pe "a-b" cu 3)
5 × 3 = 15 => 5a - 5b = 15
Alte întrebări interesante
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă